In-orbit operation of an atomic clock based on laser-cooled 87Rb atoms - Liang Liu (Nature Portfolio, 2018)
Cold atom clocks are among the most precise measuring devices and play key roles in everyday life and scientific explorations. Here the authors demonstrate the first in-orbit atomic clock using cold Rb atoms operating in microgravity and opening possibilities of space surveys and tests of fundamental physics.